An Asymmetrically Substituted Aliphatic Bis-Dithiolene Mono-Oxido Molybdenum(IV) Complex With Ester and Alcohol Functions as Structural and Functional Active Site Model of Molybdoenzymes - Ahmadi, Mohsen; Fischer, Christian; Ghosh, Ashta C.; Schulzke, Carola (Frontiers in Chemistry, 2019)
A MoIV mono-oxido bis-dithiolene complex, [MoO(mohdt)2]2− (mohdt = 1-methoxy-1-oxo-4-hydroxy-but-2-ene-2,3-bis-thiolate) was synthesized as a structural and functional model for molybdenum oxidoreductase enzymes of the DMSO reductase family. It was comprehensively characterized by inter alia various spectroscopic methods and employed as an oxygen atom transfer (OAT) catalyst. The ligand precursor of mohdt was readily prepared by a three-step synthesis starting from dimethyl-but-2-ynedioate. Crystallographic and 13C-NMR data support the rationale that by asymmetric substitution the electronic structure of the ene-dithio moiety can be fine-tuned. The MoIVO bis-dithiolene complex was obtained by in situ reaction of the de-protected ligand with the metal precursor complex trans-[MoO2(CN)4]4−. The catalytic oxygen atom transfer mediated by the complex was investigated by the model OAT reaction from DMSO to triphenylphosphine with the substrate transformation being monitored by 31P NMR spectroscopy. [MoO(mohdt)2]2− was found to be catalytically active reaching 93% conversion, albeit with a rather low reaction rate (reaction time 56 h). The observed overall catalytic activity is comparable to those of related complexes with aromatic dithiolene ligands despite the novel ligand being aliphatic in nature and originally perceived to perform more swiftly. The respective results are rationalized with respect to a potential intermolecular interaction between the hydroxyl and ester functions together with the electron-withdrawing functional groups of the dithiolene ligands of the molybdenum mono-oxido complex and equilibrium between the active monomeric MoIVO and MoVIO2 and the unreactive dimeric MoV2O3 species.